Isolating High Antimicrobial Ability Lignin From Bamboo Kraft Lignin by Organosolv Fractionation - Yun, Jinyan; Wei, Liao; Li, Wei; Gong, Duqiang; Qin, Hongyu; Feng, Xiujing; Li, Guojiang; Ling, Zhe; Wang, Peng; Yin, Baishuang (Frontiers in Bioengineering and Biotechnology, 2021)
Lignin from different biomass possesses the biological activities of antioxidation and antimicrobial activities, which is depended on the numbers of functional groups and molecular weight of lignin. In this work, organosolv fractionation was carried out to prepare the lignin fraction with a suitable structure to tailor the excellent biological activities. Gel permeation chromatography (GPC) analysis showed a decreased molecular weight lignin fractions were obtained by sequentially organosolv fractionation with anhydrous acetone, 50% acetone and 37.5% hexanes. Nuclear magnetic resonance(NMR) results indicated that the lignin fractions with lower molecular weight had fewer substructures and higher phenolic hydroxyl contents, which is positively correlated to their antioxidation ability. Both of the original lignin and fractionated lignins possessed the ability to inhibit the growth of gram-negative bacterias (Escherichia coli and Salmonella) and gram-positive bacterias (Streptococcus, and Staphylococcus aureus) by destroying the cell wall of bacterial in vitro, in which the lignin fraction with the lowest molecular weight and highest phenolic hydroxyl contents (L3) showed the best performance. Besides, L3 lignin showed ability to ameliorate E. coli treated diarrhea damages of mice to improve the formation of intestinal contents in vivo. These results imply that the lignin fraction with tailored structure from bamboo lignin can be used as the novel antimicrobial agent in the biomedical field.